Disaster impacts on co-management networks: longitudinal and comparative analysis of Chilean small-scale fisheries - Marín, Andrés; Bodin, Örjan; Gelcich, Stefan; Castilla, Juan Carlos (Frontiers in Marine Science, 2023)
Recent studies have highlighted the relational nature of co-management and investigated which kinds of social network structures define its possibilities to perform, adapt and deal with uncertainty and change. However, there is less understanding about the impacts of disasters and abrupt perturbations on co-management networks. Here we present a social network analysis of the impacts of the 2010 tsunami on co-management in the Chilean fishery. Based on data collected in 21 fisher organizations in the Bio-Bío region, heavily impacted by the tsunami, we assess whether and how co-management facilitating and hindering social relationships have changed after the event, as compared to 16 non-impacted organizations in the Valparaíso region. Baseline data (i.e., 2008) from both regions allows for before-after longitudinal analysis. Our findings show that after the tsunami, co-management networks in Bio-Bío present reduced fragmentation and higher levels of perceived trust among actors in comparison to the non-affected region. A slightly lower tendency towards decentralization was also observed. These findings suggest that post-disaster adjustments have occurred within the same networks. Co-management networks were flexible enough to be rewired as a consequence of abrupt perturbations triggered by the tsunami. Participatory network-based interventions, such as the Chilean MEABR co-management policy, provide a stable and at the same time adaptive setting to respond to coastal disasters.